Survey Implementation Curriculum 2013 in Sports and Health Physical Education Lessons at State Vocational School in District Sampang - M. Imam Yusuf W; Advendi Kristiyandaru; Heryanto Nur Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the implementation of PBL, PjBL, DL learning models and learning outcomes in PJOK subjects. This research was carried out in 3 schools that implemented the 2013 Curriculum with a research sample of 3 teachers and 283 students at State Vocational Schools throughout Sampang District. This research is a quantitative research with a survey design, the research sampling technique uses random sampling. The instruments used in this study were questionnaires, interview guidelines, observation sheets and cognitive tests. Data analysis used one way annova analysis and multiple linear regression through SPSS version 15. The results showed that the implementation of PBL learning for students in State Vocational High Schools in Sampang District was included in the good category with an average score of 100.8, the percentage was 69.52%; the implementation of PjBL learning for students in State Vocational High Schools throughout Sampang District is included in the good category with an average score of 96.13, the percentage is 66.30%; The implementation of DL learning for students at State Vocational Schools throughout Sampang District is included in the good category with an average score of 26.75, a percentage of 76.43%, and through multiple linear regression tests it can be concluded that the PBL, PjBL, and DL learning models of State Vocational High School students throughout -Sampang District is proven to affect learning outcomes with a contribution of 25%; R^2 = 0.250; F_table(3.279) = 26.37; p < 0.01. The conclusion is that data analysis of PJOK learning outcomes at State Vocational Schools in Sampang District using the PBL, PjBL, and DL learning models can improve student learning outcomes, as evidenced by the average PJOK score of 80, the interval score of ability to work on PTS questions for State Vocational High School students throughout -Sampang District is in the interval of 70 to 80; and completeness of classical learning outcomes above 80%. The results of the regression test also found that the PBL learning model (β = 0.389; p < 0.01) had a stronger effect on learning outcomes than the PjBL learning model (β = 0.229; p < 0.01) while the DL learning model had no significant effect on learning outcomes.